A Comparison between Teacher centered and Student Centered Medical Education Approach: An experimental research - Ehsan Rathore, Farhan Riaz, Nabeela Habib, Omair Anjum, Rubbab Zahra, Muhammad Behzad Salahuddin (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To investigate the comparison between teacher centered and Student centered medical education approach among multiple medical and dental institutes of Lahore. Methods: A thorough investigation was done by collecting data on results of students given Teacher centered medical education and Student centered medical education. Students of each class were divided into 5 groups and given tasks of presenting on given topics and individual students’ participation was encouraged in each group. Results: The results of teacher centered teaching showed that 20% of class scored above 80% marks. 78% of class scored between 60% and 80% marks and 2% scored less than 60% marks. On the other hand the student centered presentation had an excellent outcome where 100% of students scored more than 80% marks, out of which 60% scored more than 90%. Conclusion: It is concluded that Students’ performance in student centered medical education was higher than that in teacher centered education. This teaching technique was seen to be better retentive because of active participation of students. MeSH Words: Medical Education, Self-centered learning, Student centered learning, teacher centered learning.